Management of sleep disorders in psychiatry - Chopra, Amit; Das, Piyush, MD; Doghramji, Karl (New York, NY : Oxford University Press, 2020)
This text educates the reader on the basics of sleep medicine, clinical features and treatments of common sleep disorders, and the management of sleep disorders within a wide range of psychiatric disorders. This clinically oriented book provides case vignettes, key clinical pearls, and a self-assessment section to help readers firmly grasp clinical skills and prepare for board and certification exams.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 15, 2020).
Keywords: Sleep disorders